Reconstruction of midface defects with the osteocutaneous radial forearm flap: Evaluation of long term outcomes including patient reported quality of life. Issue 7 (26th August 2017) - Connolly, Timothy M.; Sweeny, Larissa; Greene, Benjamin; Morlandt, Anthony; Carroll, William R.; Rosenthal, Eben L.
Abstract: Background: Maxillectomy defects significantly impair quality of life. Prosthetics can overcome some of these issues, but has limitations. The role of the osteocutaneous radial forearm free flap (OC‐RFFF) has been established for reconstruction of smaller maxillectomy defects, but its role in larger defects is not well defined. We aim to evaluate outcomes after midface reconstruction utilizing the OC‐RFFF. Methods: Retrospective review of prospective database collected between 2005 and 2014 of midface reconstruction using OC‐RFFF in a tertiary care centre. Donor site complications and acute and long‐term recipient site complications were measured. Health related quality of life was assessed using the University of Washington Quality of Life (UW‐QOL) Questionnaire. Results: A total of 68 midface defects were reconstructed using the OC‐RFFF. Acute recipient site complications included three flap failures (4%), and two additional microvascular revision cases for vascular compromise. Late recipient complications included fistula ( n = 10, 14%), ectropion ( n = 7, 10%), diplopia ( n = 6, 9%) and exposed hardware ( n = 5, 7%). Resection of cheek skin or orbital rim correlated with orbital complications. The incidence of fistula was not affected by defect size or prior radiation. There were two donor site infections and no instances of forearm fracture. Patients undergoing OC‐RFFF repair had mean scores for UW‐QOL outcomes higher than published rates of obturator quality of life. Conclusion: The OC‐RFFF is suited to a variety of midface defects and can be combined with hardware to reconstruct the orbital floor. Recipient site complications are common, but donor site morbidity is low and outcomes, including HR‐QOL, are acceptable.